Micronutrient content in enteral nutrition formulas: comparison with the dietary reference values for healthy populations. Issue 1 (December 2015) - Iacone, Roberto; Scanzano, Clelia; Santarpia, Lidia; D'Isanto, Anna; Contaldo, Franco; Pasanisi, Fabrizio
Abstract Background The micronutrient content in standard enteral mixtures should be closer to the dietary reference values for a healthy population since standard enteral diets are formulated for subjects with no special nutritional needs. This study compares the micronutrient content of the most common enteral nutrition (EN) formulas with European dietary reference values (DRVs) for healthy population. Findings Sixty-two nutritionally complete enteral formulas were considered. The micronutrient content was calculated by multiplying the value reported on the nutritional information panel of each formula by the daily dose usually prescribed. The comparison between the micronutrient content of all enteral formulas evaluated and the DRVs indicates that daily fluoride and vitamin K requirements were not covered, while an oversupply of many other micronutrients was provided. Moreover, in some enteral formulas, at a dose of 2000 Kcal/day, zinc and vitamin A content exceeded the tolerable upper limits and, for one diabetes-specific enteral formula, the chromium content exceeded the relevant European standards in both 1500 and 2000 Kcal/day diets. Conclusions Most enteral formulas evaluated are generally suitable for patients on long-term total EN and formulas with higher content of a specific micronutrient may be a useful tool for patients affected by specific clinical conditions, at least for a period of time, then switching to standard enteral mixtures. The availability of nutritional enteral formulas, well balanced also for micronutrient intake, will further improve individualized treatments, particularly for patients on long-term total EN.